An analysis of genetic variability in two open-pollinated maize varieties and their cross - Gevers, H. O.(Helmut Otto) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1962.